2021
DOI: 10.3390/ijms22073750
|View full text |Cite
|
Sign up to set email alerts
|

CHOP Pro-Apoptotic Transcriptional Program in Response to ER Stress Is Hacked by Zika Virus

Abstract: Zika virus (ZIKV) is an emerging mosquito-borne flavivirus considered as a threat to human health due to large epidemics and serious clinical outcomes such as microcephaly in new-borns. Like all flaviviruses, ZIKV relies on the cellular machinery to complete its viral cycle, with the endoplasmic reticulum (ER) being the critical site of viral replication factories. The sudden high protein load in the ER induces an ER stress to which the cell responds with an appropriate unfolded protein response (UPR) in an at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 59 publications
4
23
0
Order By: Relevance
“…A privileged role for Bcl-2-family of anti-apoptotics was confirmed by the use of the inhibitor ABT-737, which abrogated ZIKV-mediated protection, led to restoration of apoptosis and reduced viral infection [90]. As previously mentioned, we also found that ZIKV was able to subvert the CHOP pro-apoptotic program and thus override ERdependent apoptosis [94]. This viral ability to inhibit one of the main cellular defense responses to infection legitimately raises the question of its effect on the outcome of infection and, if unsuccessful, the possibility that the virus will not be properly eliminated.…”
Section: Is Delayed and Impaired Apoptosis Responsible For Zikv Persistence And Unusual Transmission Pathways?supporting
confidence: 81%
See 1 more Smart Citation
“…A privileged role for Bcl-2-family of anti-apoptotics was confirmed by the use of the inhibitor ABT-737, which abrogated ZIKV-mediated protection, led to restoration of apoptosis and reduced viral infection [90]. As previously mentioned, we also found that ZIKV was able to subvert the CHOP pro-apoptotic program and thus override ERdependent apoptosis [94]. This viral ability to inhibit one of the main cellular defense responses to infection legitimately raises the question of its effect on the outcome of infection and, if unsuccessful, the possibility that the virus will not be properly eliminated.…”
Section: Is Delayed and Impaired Apoptosis Responsible For Zikv Persistence And Unusual Transmission Pathways?supporting
confidence: 81%
“…However, if we and others have noticed a significant increase in the transcriptional expression of CHOP [88], there is a lack of information concerning the CHOP protein presence in ZIKV infected cells. Thus, in the A549 model, we showed that the CHOP factor and its pro-apoptotic translational program were not induced [94]. Assessment of its role in the virally induced UPR-dependent apoptosis is therefore difficult.…”
Section: Is Early Apoptosis In Development Responsible For the Irreversible Damage Produced By Zikv Infection?mentioning
confidence: 87%
“…However, if we and others have noticed a significant increase in the transcriptional expression of CHOP [104], there is a lack of information concerning the CHOP protein presence in ZIKV infected cells. Thus, in the A549 model, we showed that the CHOP factor and its pro-apoptotic translational program were not induced [92]. Assessment of its role in the virally induced UPR-dependent apoptosis is therefore difficult.…”
Section: Zika Virus and Apoptosismentioning
confidence: 87%
“…In the middle and late stages of virus infection, a large number of viruses replicate in the target cells, and activate mitochondrial and endoplasmic reticulum stress and other apoptosis pathways, leading to cell apoptosis. The flaviviruses infection is capable of triggering multiple apoptotic pathways, such as mitochondria-dependence ( Suzuki et al., 2018 ), death receptor ( Liao et al., 2010 ), and endoplasmic reticulum ( ER ) stress ( Huang et al., 2016 ; Turpin et al., 2021 ). JEV triggered apoptosis of N18 (a mouse neuroblastoma cell line) cells through the mitochondrial pathway ( Tsao et al., 2008 ), possibly by inducing proteolysis of endogenous p21 BAX to produce p18 BAX in SH-SY5Y cells (human neuroblastoma) ( Wongchitrat et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…JEV plays a role in cell apoptosis through p38-dependent and transcription factor C/EBP homologous protein ( CHOP ) mediated pathways ( Su et al., 2002 ). ZIKV impaired the expression of CHOP/DDIT3, which is the main factor of ER-stress-driven apoptosis ( Turpin et al., 2021 ). JEV infection decreased Forkhead box O ( FoxO ) expression both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%